Economic comparison of power and chilled water generation by cogeneration system and public utility - Nordin, A. (EDP Sciences, 2014)
The paper presents an economic comparative study on the electricity and chilled water generation between using cogeneration system and public utility. A comparative evaluation using Net Present Value method was adopted in this study. The study shows that using cogeneration system is economically feasible compared to PU if the failure frequency per year is 5 or less. Â© 2014 Owned by the authors, published by EDP Sciences.